Prevalence and risk factors of chemotherapy- induced oral mucositis among adult cancer patients at the cancer unit of Mbarara Regional Referral Hospital - Atwiine, Fredrick; Kyomya, Julius; Atukunda, Esther C.; Isiiko; Yadesa, Tadele Mekuriya (Asia‐Pacific Journal of Clinical Oncology, 2024)
Background: Chemotherapy is a common treatment for cancer, but it is associated with adverse drug reactions like oral mucositis. This condition destroys basal cells in the oral mucosal layer, causing inflammation and ulceration. This can impact the patient’s physical, emotional, and psychological well-being, affecting treatment outcomes and quality of life. This study aims to determine the prevalence, severity, and risk factors of chemotherapy-induced oral mucositis among adult cancer patients. Methods: The study was a cross-sectional study conducted among adult cancer patients receiving chemotherapy at the cancer unit of Mbarara Regional Referral Hospital in southwestern Uganda. Data was collected through patient interviews, oral examinations, and patient chart reviews. Results: Out of 268 patients, 115 (42.9%) experienced oral mucositis. Grade 2 oral mucositis was the most common (44.3%) followed by grade 1 (35.7%) and grade 3 (20.0%). Independent risk factors of chemotherapy-induced oral mucositis were female gender (Adjusted Odds Ratio (AOR) = 2.19, 95% confidence interval [CI]: 1.27–3.78; p-value = 0.005), poor oral hygiene (AOR = 3.70, 95% CI: 1.51–9.10; pvalue = 0.04), and receiving chemotherapy containing an alkylating agent (AOR = 3.17, 95%CI:1.63–6.19; p-value < 0.001). Conclusion: The study found that two out of five chemotherapy patients developed oral mucositis, with nearly half being grade 2. The risk factors identified in our study were comparable to those reported in previous studies. Therefore, identification and assessment of cancer patients at high risk for chemotherapy-induced oral mucositis should be routinely done for proper and timely management
Keywords: Cancer; Chemotherapy; Mbarara; Oral mucositis; Prevalence